Herpes zoster in a 10-month-old girl. - Christopher, P.M.; Jayadi, N.N.; Warouw, M.; Tan, S.; Enggalhardjo, M.; Damar, H.K.T.M.; Adjie, H.K. (European Journal of Pediatric Dermatology, 2022)
Primary varicella-zoster virus (VZV) infection typically affects children, while Herpes zoster (HZ) affects adults, and most patients are over the age of 50 (2). In the present case, VZV was acquired in utero by vertical mother-to-fetus transmission. Vertical transmission of VZV can occur in three ways: 1) transplacental viremia, 2) direct contamination during delivery, and 3) postnatal contamination (1). The risk of fetal VZV infection is related to several factors, including the intensity of exposure to the virus, the amount of placental antibodies transferred from the mother to the baby, and the seropositivity of the mother at delivery […].